Concept of Ḡarar in the Muslim Legal, Theological and Economic Thought (Economic and Political Thought, 2013)
Ḡarar is one of the least known and most misunderstood concepts inIslamic Banking and Finance. Both Islamic scholars of the classical periodand contemporary researchers attempted to coin its commonly accepted definition.By far no one has managed to succeed, though. The most prevalenttranslation of ḡarar is ‘risk’. However, I am proving in the article that thetranslation is inadequate and misleading. Relying on two major sources oflaw in Islam: Koran and Sunnah of Muhammad as well as classical and contemporaryworks by Muslim and secular scholars, I discuss the most commondefinitions of the term and the social and historical context in which the ḡararban came into existence. I also attempt to create a broader definition thatcould help understand the essence of ḡarar and the reasons why it is banned.